Consumption Analysis of Children with Lack Nutrition at the Patient Health Center - Berliana, Suci Wahyu; Subekti, Sri; Nikmawati, Ellis Endang; Mupita, Jonah (Universitas Pendidikan Indonesia (UPI), 2021)
The number of malnutrition toddlers still exceeds the minimum number set on a national scale in Indonesia. Malnutrition occurs because of the lack of diversity in food consumption and fulfillment of energy and macronutrients in the consumption. The purpose of this research was to determine the diversity of food consumption and the level of fulfillment of energy consumption in malnutrition toddlers. The method in this research is the descriptive-analytical method with a quantitative research approach. The sampling technique uses total sampling, which includes all members of the population as samples. Diversity of consumption and level of energy fulfillment were obtained by interview using food frequency questionnaire and food recall 2x24 hours. The results of the research based on the diversity of consumption showed that the types of food commonly consumed by toddlers were rice (staple food); eggs, chicken, and fish (animal side dishes); tofu and tempeh (vegetable side dishes); spinach and carrots (vegetables); and papaya and banana (fruits). Based on the results of research on the level of energy fulfillment, as many as 39 toddlers have a deficit in energy consumption, 13 toddlers have a protein consumption deficit, 32 toddlers have a fat deficit, and 25 toddlers have a carbohydrate deficit. Recommendations in this research are addressed to the hospital to conduct outreach activities regarding knowledge of the diversity of food consumption and nutrients in foodstuffs.